Response of Oil Palm Varieties to Aluminium Stress - Nanang Supena (Journal of Tropical Life Science, 2014)
Aluminum (Al) will be toxic to plants when soil is very acid. Soil reaction on acid condition tends to turn Al into trivalent cation (Al3+) disturbing the function of the root end cells in doing the division and elongating the function. Today, the study of Al stress on crop trees as oil palm is very little. This research was aimed to study the growth of oil palm varieties in growing media treated Al stress. The experiment was conducted in the screen house using a randomized block design with two treatments, oil palm varieties and concentrations of Al. Varieties consisted of five oil palm progenies (OPP) i.e. PPKS239, PPKS540, PPKS718, Simalungun, and Dumpy. They were planted into the sterile sand medium in the form of sprouts and Al was treated with five different concentrations, 0, 75, 150, 225, and 300 ppm. Al was applied at the same time in the plant from 4 to 12 weeks after planting. Observations were conducted on several morphological and physiological variables at shoots and roots. The results showed a significant interaction between varieties and Al on the length of primary roots and reducing sugar content. The average of reducing sugar content was 24% less from control than it was when treated by Al 300 ppm. Simalungun varieties had more tolerant to Al than others. The length of Simalungun primary roots was more stable when the concentration of Al was 300 ppm whereas PPKS718 and PPKS540 varieties were decreased 24.3 and 12.4% respectively. The tolerance of Simalungun was also marked from reducing sugar content which was lower than other varieties. According to Koch (2004), the low content of reducing sugar when given Al was an indication of plant resistance mechanisms against Al toxicity where the number of sugar was transported from roots to the shoots for immobilizing Al. Consequently, it decreased sugar content in the shoot.